Ketahanan Ekonomi Nasional Masa dan Pasca Covid-19 Melalui Penguatan UMKM Indonesia: (National Economic Resilience During and Post-Covid-19 Through Strengthening Indonesian MSMEs) - Arman Arman; Ni Nyoman Sawitri; Asep Saefuddin (UPT Penerbitan Universitas Jember, 2023)
The Coronavirus disease-19 (Covid-19) crisis has an impact on the economic performance of Micro, Small and Medium Enterprises (MSMEs) at local and national levels. MSME actors are trying to survive the crisis through business efficiency and the national economic rescue program (PEN). This paper aims to (1) examine the resilience of MSMEs against a wave of crisis (2) the right policy formula to strengthen the competitiveness of MSMEs. This research uses descriptive qualitative method using secondary data. The data is sourced from the Ministry of Small and Medium Enterprises Cooperatives, Bank Indonesia (BI), the Central Statistics Agency (BPS), the National Planning and Development Agency (Bappenas), national and international scientific journals and media sources. Slowly, the condition of MSMEs began to rise from the Covid-19 crisis through the PEN program policy which ran in September-December 2020, economic growth was better in the fourth quarter of 2020 by -2.19 percent (yoy), better than the growth in the third quarter 2020 by -3.49 percent (yoy). The distribution of the PEN program for MSMEs was successful and effective in maintaining the resilience of MSMEs from the Covid-19 crisis. The government needs to maintain economic momentum, through the synergy of MSMEs with State-Owned Enterprises (BUMN), digitalization and the MSME global supply chain as well as increasing the PEN budget for MSMEs. On the other hand, the government still has a tough task to cut logistics costs which are still relatively high when compared to several ASEAN countries.